ANALISIS FAKTOR PENYEBAB TINGGINYA CERAI GUGAT DI PENGADILAN AGAMA MATARAM KELAS 1A - Andilia Santika; Anjeun Renyta Agatin; Baiq Nunung; Dila Aprillia; Lina Fitriani; Lalu Sumardi; Nirwan Samsul Rijal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Divorce remains one of the major issues in family law in Indonesia due to its significant impact on family resilience, children's well-being, and social stability. In recent years, divorce petitions filed by wives (cerai gugat) have constituted the majority of divorce cases handled by the Religious Courts, including the Mataram Class IA Religious Court. This study aims to analyze the factors contributing to the high number of cerai gugat cases at the Mataram Class IA Religious Court. This research employed a qualitative method with a case study approach and was conducted as an empirical legal study. Data were collected through interviews with judges and court clerks, direct observations during the researcher's internship, documentation, and literature review. The collected data were analyzed using descriptive qualitative analysis. The findings indicate that the high number of cerai gugat cases is influenced by several interrelated factors, including continuous marital disputes and conflicts, economic problems, infidelity, domestic violence, and the husband's failure to fulfill his responsibilities toward his wife and children. Among these factors, continuous marital disputes and conflicts emerged as the most dominant reason for filing divorce petitions. However, these disputes generally resulted from underlying problems, particularly financial difficulties, infidelity, and the husband's neglect of his legal and moral obligations within the family. Therefore, efforts to reduce the number of cerai gugat cases should focus on strengthening family resilience, improving ommunication between spouses, optimizing mediation services in the Religious Courts, and increasing public awareness of the rights and obligations of husbands and wives in marriage